2015
DOI: 10.1021/acsami.5b05238
|View full text |Cite
|
Sign up to set email alerts
|

Activating Aluminum Reactivity with Fluoropolymer Coatings for Improved Energetic Composite Combustion

Abstract: Aluminum (Al) particles are passivated by an aluminum oxide (Al2O3) shell. Energetic blends of nanometer-sized Al particles with liquid perfluorocarbon-based oxidizers such as perfluoropolyethers (PFPE) excite surface exothermic reaction between fluorine and the Al2O3 shell. The surface reaction promotes Al particle reactivity. Many Al-fueled composites use solid oxidizers that induce no Al2O3 surface exothermicity, such as molybdenum trioxide (MoO3) or copper oxide (CuO). This study investigates a perfluorina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(69 citation statements)
references
References 36 publications
1
68
0
Order By: Relevance
“…The measured burning rate results, listed in Table 1, were comparable to results obtained in other studies [12,16]. Filaments extruded for 3D printable compositions based on PVDF, with 20 wt.% aluminium as fuel, exhibited burning rates of up to 18.7 ±1.3 mm•s −1 [12].…”
Section: Burn Rate and Time To Ignitionsupporting
confidence: 85%
See 2 more Smart Citations
“…The measured burning rate results, listed in Table 1, were comparable to results obtained in other studies [12,16]. Filaments extruded for 3D printable compositions based on PVDF, with 20 wt.% aluminium as fuel, exhibited burning rates of up to 18.7 ±1.3 mm•s −1 [12].…”
Section: Burn Rate and Time To Ignitionsupporting
confidence: 85%
“…Filaments extruded for 3D printable compositions based on PVDF, with 20 wt.% aluminium as fuel, exhibited burning rates of up to 18.7 ±1.3 mm•s −1 [12]. Potgieter et al [16] measured the burning rates of energetic films based on Viton B fluoropolymer as oxidant with 50 wt.% metal fuel.…”
Section: Burn Rate and Time To Ignitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoro-polymers such as polytetrafluoroethylene (PTFE) and perfluoropolyether (PFPE) have even been shown to be capable of improving the oxidation efficiency of Al particles because fluorine atoms decompose the alumina shell surrounding the Al particles into AlF 3 products 2124 . Once the internal Al material is continuously exposed as fluorine-compounds are formed and evaporated, the oxidation reaction proceeds efficiently compared to that with pure Al particles with a dense surface oxide that inhibits continuous combustion 25, 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Shaw et al. also has shown that a B 4 C/NaIO 4 system with the addition of a fluoropolymer binder, polytetrafluoroethylene (PTFE), can result in halogenated fumigants . The versatility of B 4 C as a fuel has also been shown by Shaw et al.…”
Section: Introductionmentioning
confidence: 90%